Toleransi dan Kearifan Lokal Suku Bugis di Perantauan: Studi Kasus di Kabupaten Malaka, Nusa Tenggara Timur - Maesurah, Sitti; Klau, Stanis (Universitas Batanghari Jambi, 2025)
This research aims to understand the role of local wisdom and religious moderation in creating social harmony among the Bugis community who live in Malaka Regency, East Nusa Tenggara. This research uses a qualitative approach, because it is in accordance with the research objectives which are to explore and understand the experiences and perspectives of research subjects in the context of social and cultural life. Research data collection was carried out through interviews and direct observation in the field. The results of this research found that: (1) the local wisdom of the Bugis tribe, especially the concept of siri' na pacce, is the main basis for maintaining self-respect and social solidarity; (2) the Bugis community in Malacca Regency shows a strong attitude of religious moderation, where they are able to carry out religious teachings while still respecting and appreciating the differences in religious beliefs around them; and (3) the Bugis community plays an active role in creating and maintaining social harmony in Malacca Regency through involvement in social, economic and religious activities.